2020
DOI: 10.1108/cdi-09-2018-0226
|View full text |Cite
|
Sign up to set email alerts
|

Voice and silence as immediate consequences of job insecurity

Abstract: Purpose The purpose of this paper is to examine the weekly effects of job insecurity on employee voice and silence. Specifically, the authors argue that because employment fulfils important needs, employees’ needs are less fulfilled when they feel that their job is at risk (i.e. high job insecurity). Consequently, the authors argue that employees engage in less voice and more silence because when employees’ needs are not fulfilled, they are less committed to the organization and/or protect their personal resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 72 publications
3
34
0
Order By: Relevance
“…In addition, based on the resource conservation theory, some researchers found that due to the limitation of internal resources, individuals usually lack sufficient energy and resources to cope with external pressure, resulting in reduced engagement [30]. Employment as a demand, when employees are aware that their work is in a dangerous state (that is, a high degree of job insecurity), that is, their needs are threatened or cannot be met, individuals tend to protect their own resources and reduce the input of work resources [4]. Secondly, job insecurity can induce individuals to produce emotions such as anxiety, complaint and depression, and these adverse emotional reactions will lead to deviant behaviors to varying degrees.…”
Section: Job Insecurity and Employee Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, based on the resource conservation theory, some researchers found that due to the limitation of internal resources, individuals usually lack sufficient energy and resources to cope with external pressure, resulting in reduced engagement [30]. Employment as a demand, when employees are aware that their work is in a dangerous state (that is, a high degree of job insecurity), that is, their needs are threatened or cannot be met, individuals tend to protect their own resources and reduce the input of work resources [4]. Secondly, job insecurity can induce individuals to produce emotions such as anxiety, complaint and depression, and these adverse emotional reactions will lead to deviant behaviors to varying degrees.…”
Section: Job Insecurity and Employee Engagementmentioning
confidence: 99%
“…A large number of studies have shown that job insecurity has become a common source of stress for employees. On the one hand, negative workplace effects caused by job insecurity, such as turnover intention [3], workplace silence [4], workplace bullying [5], etc., that will undermine the organization's human resource management system, thus affecting the sustainable development of the organization. On the other hand, employees' mental health problems caused by job insecurity, such as emotional exhaustion [6], anxiety [7], etc., that will destroy the family harmony of employees, lead to a decline in health and quality of life, and have an impact on social stability and sustainable development [8].…”
Section: Introductionmentioning
confidence: 99%
“…Based upon theory and research on employee voice and silence (Hirschman, 1970), we expect that workers who are worried about potential job loss may be more hesitant to voice concerns about potential COVID‐19 risks. Indeed, research suggests that job insecurity is associated with a decrease in the use of voice (Berntson, Näswall, & Sverke, 2010; Breevaart, Lopez Bohle, Pletzer, & Muñoz Medina, 2020; Schreurs, Günter, Jawahar, & de Cuyper, 2015); moreover, such silence on the part of employees is understandable considering research findings that supervisors view employees who challenge (rather than affirm) them as a potential threat (Burris, 2012). Thus, employees already fearful of potential job loss may be less likely to speak out against perceived health and safety risks.…”
Section: Introductionmentioning
confidence: 99%
“…With increasingly fierce competition prevalent in the external environment, enterprises pay more attention to employee voices since such behavior can promote their competitive advantages. As in the micro foundation of enterprises, employees are more likely to experience the deficiencies of managers' orders and find existing problems in corporations (Benevene, 2020;Breevaart et al, 2020). However, many employees choose to keep silent and do not give feedback on the problems they find due to various factors (Morrison and Milliken, 2000;Whiteside and Barclay, 2013;Prouska and Psychogios, 2018).…”
Section: Introductionmentioning
confidence: 99%